Designing Trade Cooperation under Regime Complexity: A Rational Design Analysis of the Indonesia-Korea Comprehensive Economic Partnership Agreement - Ilham Dary; Hayara Khairia; Tsabita Husna (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2026)
This article examines the Indonesia–Korea Comprehensive Economic Partnership Agreement (IK-CEPA), which entered into force on 1 January 2023, as a case of bilateral trade cooperation within an increasingly complex regional trade environment. The study investigates how the institutional design of IK-CEPA supports economic cooperation and governance between Indonesia and South Korea. Drawing on liberal institutionalism and rational design theory, the research employs qualitative content analysis of the agreement’s legal provisions, supported by implementation documents and official trade and investment data. The findings show that IK-CEPA extends beyond tariff liberalization by establishing formal coordination mechanisms, review procedures, and economic cooperation programs that facilitate policy coordination and capacity-building between the two countries. Early implementation indicates modest changes in bilateral trade performance but stronger continuity in investment cooperation, suggesting that the agreement’s governance functions may be more significant in the short term than its immediate trade effects. This study contributes to the literature by demonstrating how bilateral trade agreements can complement existing regional frameworks and strengthen economic governance through targeted institutional arrangements.